BASIC PENTACYSTEINE1 regulates ABI4 by modification of two histone marks H3K27me3 and H3ac during early seed development of Medicago truncatula - Dang, Thi Thu; Lalanne, David; Ly Vu, Joseph; Ly Vu, Benoit; Defaye, Johan; Verdier, Jerome; Leprince, Olivier; Buitink, Julia (Frontiers in Plant Science, 2024)
The production of highly vigorous seeds with high longevity is an important lever to increase crop production efficiency, but its acquisition during seed maturation is strongly influenced by the growth environment. An association rule learning approach discovered MtABI4, a known longevity regulator, as a gene with transcript levels associated with the environmentally-induced change in longevity. To understand the environmental sensitivity of MtABI4 transcription, Yeast One-Hybrid identified a class I BASIC PENTACYSTEINE (MtBPC1) transcription factor as a putative upstream regulator. Overexpression of MtBPC1 led to a modulation of MtABI4 transcripts and its downstream targets. We show that MtBPC1 represses MtABI4 transcription at the early stage of seed development through binding in the CT-rich motif in its promoter region. To achieve this, MtBPC1 interacts with SWINGER, a sub-unit of the PRC2 complex, and Sin3-associated peptide 18, a sub-unit of the Sin3like deacetylation complex. Consistent with this, developmental and heat stress-induced changes in MtABI4 transcript levels correlated with H3K27me3 and H3ac enrichment in the MtABI4 promoter. Our finding reveals the importance of the combination of histone methylation and histone deacetylation to silence MtABI4 at the early stage of seed development and during heat stress.